Institutionalization of Maritime Domain Awareness (MDA) Development in Government Policy - Narahara, Sean; Suseto, Buddy; Alam, Tasdik Mustika (Formosa Journal of Applied Sciences, 2024)
The concept of Maritime Domain Awareness (MDA) is significant for the government to implement in order to form an effective understanding of Indonesia's maritime domain. In this regard, in the 2014-2022 period, the government has issued 3 policies related to MDA, such as establishing the Maritime Security Agency (Bakamla) of the Republic of Indonesia through the issuance of Law No. 32 of 2014 concerning Maritime Affairs, forming a Joint Agreement on the Exchange of Data and Information in the Framework of Law Enforcement at Sea. Considering the quantity of policies that have been issued and the failure to form MDA in Indonesia, it is necessary to analyze the institutional framework arrangements in these policies.